(untitled) (Journal of International Crisis and Risk Communication Research, 2021)
The field of crisis and risk communication research has experienced significant growth and increasing institutionalization in the past decades. However, there are still geographic and perspective blind spots. Up to date, by far the most research focuses on the U.S.; non-Western perspectives remain marginal. Moreover, the focus on organizational crises still clearly dominates. We therefore call for more research better reflecting the global environment and diverse crisis and risk contexts in which our field can make contributions. This argument is supported by the current pandemic mandating cross-cultural and multi-perspective approaches.